A Compressed Sensing-Based Element Failure Diagnosis Method for Phased Array Antenna During Beam Steering - Xiong, Can; Xiao, Gaobiao; Hou, Yibei; Hameed, Musab (IEEE antennas and wireless propagation letters, 2019)
A novel diagnosis method for phased array antenna element failure using near-field measurements based on compressed sensing is proposed. In consideration of the beam steering property of phased arrays, sampling of the radiated field is performed with fixed probes. The independence of received field data is attained in the phase domain instead of the conventional spatial domain. It yields a new way to construct the sensing matrix and, hence, the measurement vector. This strategy enables onsite diagnosis while the array under test is still scanning regularly. The reconstruction of antenna element excitations is achieved via sparse approximation methods. A nonconvex optimization algorithm is utilized to reconstruct the unknown excitation amplitudes in consideration of noise. The detection area of a single probe is limited. Arrays consisting of isotropic antennas and Hertzian dipoles are tested to verify the effectiveness of the proposed method.